Relationship between Hemodialysis Duration, Hemoglobin, and Creatinine of Hemodialysis Erythropoietin Vaccinated Patients with Covid-19 - Munuarti Muhawia; Ramatillah, Diana Laila; Sulaiman, Syed Azhar Syed (Newinera Publisher, 2025)
Chronic Kidney Disease (CKD) is an abnormality of kidney function and structure, where the glomerular filtration rate is less than 60 mL/min/1.73 m² and kidney damage lasts more than 3 months. The purpose of the study was to clarify the relationship between the length of hemodialysis with Hemoglobin and Creatinine in Hemodialysis patients. The research design used was prospective and retrospective cohort. Retrospective for the period January 2022-January 2023, while for the prospective period February-April 2024. The sample size in this study using convinienvce sampling technique was 259. The results of the study showed that there was a significant relationship between the length of hemodialysis with hemoglobin and creatinine levels with a P-value of 0.001 <0.05.